NSAIDs: Unveiling Their Role in Drug-Induced Psoriasis [Letter] - Shaikh S (Dove Medical Press, 2024)
Somina Shaikh Department of Internal Medicine, Dow Medical College, Dow University of Health Sciences, Karachi, PakistanCorrespondence: Somina Shaikh, Dow Medical College, Karachi, Pakistan, Email somina.sh16@gmail.com